The Influence of Leadership, Motivation and Work Environment on Employee Performance at PT. Citra Indah Abadi Jaya - Denis Pradana Putra Rumpaidus; Akhmad Fauzi (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Human resource management is part of organizational management that focuses on elements of human resources. In the organization, humans are one of the most important elements in an organization. Based on data in 2021, the performance of employees of PT. Citra Indah Abadi Jaya has decreased even though they have quite a lot of orders. They should have the ability to carry out their duties properly. The purpose of this study was to determine the effect of leadership, motivation and work environment on the performance of employees of PT. Citra Indah Abadi Jaya. Design/methodology/approach: In this study, the population is all employees at PT. Citra Indah Abadi as many as 40 people and the sample of this study used a saturated sample. Findings: The results showed that leadership has a positive influence on the performance of employees of PT. Citra Indah Abadi Jaya, apart from that, motivation and work environment variables also have a positive influence on the performance of PT. Citra Indah Eternal Jaya. Originality/value: This paper is an original work. Paper type: Research paper